Family Reunification: A Systematic Review of Interventions Designed to Address Co-Occurring Issues of Child Maltreatment and Substance Use. Issue 4 (20th October 2017) - Murphy, April L.; Harper, Whitney; Griffiths, Austin; Joffrion, Christopher
ABSTRACT: A significant risk factor of child maltreatment is parental substance use. In response to the burgeoning number of child maltreatment cases involving substance use, the child welfare system has created various models of intervention. Utilizing the PRISMA guidelines, a systematic literature review was conducted to identify and characterize interventions utilized by child welfare agencies seeking reunification. A search of seven electronic databases examined peer-reviewed articles published between 2006 and October 2016. Four models of intervention became apparent throughout the review, which included Family Treatment Drug Court (FTDC), Family Treatment Drug Court plus additional services (FTDC Plus), Comprehensive Services (also referred to as Wrap Around), and the Strengthening Families Program (SFP). Results suggested that the most critical aspect of successful treatment and reunification was whether parents received comprehensive services that were specifically matched to the individual, regardless of the chosen treatment model.